1958
DOI: 10.1542/peds.21.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Cystic Fibrosis of the Pancreas: Protein Pattern in Meconium Ileus

Abstract: Aqueous extracts of meconium obtained from normal children and from patients with meconium ileus were examined by means of chemical precipitation, paper electrophoresis and precipitin tests. All the extracts from patients with meconium ileus were found to contain protein which was readily precipitated by trichloracetic acid. In 59 extracts of meconium from normal infants no protein could be demonstrated by the use of trichloracetic acid. In the abnormal extracts, the major constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1959
1959
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In 1952 Buchanan and Rapoport demonstrated that the abnormally viscid meconium in babies with meconium ileus contained less carbohydrate and more protein than normal meconium [14]. In 1958 Green et al [15] reported that the major protein in meconium is albumin. This observation has subsequently been confirmed by several other authors, with some noting that the albumin concentration in meconium was rive to ten rimes higher than the levei in the meconium of unaffected neonates [16,17].…”
Section: Genetics and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1952 Buchanan and Rapoport demonstrated that the abnormally viscid meconium in babies with meconium ileus contained less carbohydrate and more protein than normal meconium [14]. In 1958 Green et al [15] reported that the major protein in meconium is albumin. This observation has subsequently been confirmed by several other authors, with some noting that the albumin concentration in meconium was rive to ten rimes higher than the levei in the meconium of unaffected neonates [16,17].…”
Section: Genetics and Etiologymentioning
confidence: 99%
“…Diez pacientes con necomium ileus no complicado fueron tratados exitosamente con enema de gastrografina. Los 15 pacientes restantes requirieron laparotomfa; en nueve se hizo resecci6n intestinal y enterostom[a y seis casos recientes fueron manejados con resecci6n intestinal y anastomosis (15) o enterostomia (20). La sobrevida a un afio fue de 92% en los pacientes con meconium ileus complicado.…”
Section: Postoperative Managementunclassified
“…Such a lack of activation of proteolytic zymogens in CF fetus is in keeping with previous data showing an absence of active proteases in CF meconium, the first example of which being an increased albumin content discovered by Green et at. (22). This observation led to the so called " BM test ," in which a strip impregnated with buffered tetrabromophenolphtalein becomes intensely blue if > 20 mg of albumin per gram (dry weight) of meconium is present.…”
Section: Discussionmentioning
confidence: 99%